Proliferation of Digital Twins: Towards new horizons of Digital Twin-technology - Jari Kaivo-oja; Mikkel Stein Knudsen; Theresa Lauraeus (Turkey, 2022)
Digital Twin (DT) technology is at the forefront of the manufacturing integration of informatization and industrialization, pairing the datafied virtual world with the physical world of advanced manufacturing. It is a digital representation mirroring real-life objects, processes or systems, and as such DT is the spearhead of rapidly developing virtual simulation technology. While the concept of Digital Twins is relatively new, attention to the technology has exploded in recent years both in academia and among businesses. This is e.g. reflected by the placement of Digital Twin at the very peak of the Gartner Hype Cycle for 2019. Grasping the opportunities provided by Digital Twin-technology is therefore paramount in order to assess the current state-of-the-art of intelligent manufacturing, but also in order to fully exploit the potential benefits of intelligent manufacturing in an Industry 4.0-society.
This paper first assesses the historical development of the Digital Twin-concept from the first proposition of the concept around 2002, through the incubation stage to the current growth stage. The paper then briefly examines the current state-of-the-art of Digital Twin in manufacturing through design, manufacturing, the use phase, and on to maintenance, repair and operation (MRO). After this, the remarkable current proliferation of the Digital Twin-concept is discussed. Now the concept is not only gradually expanding into more and more areas of the operating environment of the manufacturing industry, Digital Twin is also put to use in radically different contexts. There are increasingly Digital Twins of physical places, and DT is becoming an important tool for town planning and urban development. Smart City Digital Twins (SCDT) illuminates cities’ human-infrastructure-technology interactions, enables informed urban development choices and rapid responses to emergency situations. In 2019, the new Indian state capital Amaravanti, is thought to be the first ever city born with a Digital Twin approach. DTs are also used to simulate processes, and the idea of modelling complete operational environments for Digital Twin of an Organisation (DTO) is emerging. Also Personal Digital Twins (PDT) are appearing on the horizon as intelligent decision-assistance systems based on data algorithms and machine learning, aiding individuals in navigating through data-rich communication with machines, systems and other PDTs. Integrating digital, physical and social realms through PDTs can create superior customer experiences in both business-to-business and business-to-consumer markets and indeed fundamentally alter these markets. We can also expect that in the future novel products and services are innovated to Digital Twins, which is a novel challenge for companies and corporations. While digital twin in manufacturing and digital twins of smart cities has received significant academic attention in recent years, literature on DTOs and PDTs are hitherto very sparse. With the introduction and discussion of these concepts, the article therefore provides a significant contribution to the academic literature on digital twins.